Existence, Supervision, and Responsibility of Individual Limited Liability Company as a Legal Entity - Mangpul Sitanggang; Hendri Jayadi; Armunanto Hutahaean (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Limited Liability Companies (PT) are business entities that are in demand because they provide separation of wealth between share owners and legal entities. Through Law Number 6 of 2023 concerning Stipulation of Government Regulations in Replacement of Law Number 2 of 2022 concerning Job Creation (UU Job Creation), the provisions in Law Number 40 of 2007 concerning PTs have undergone changes, including allowing the establishment of PTs by one founder (single shareholder) for business Micro, Small and Medium Enterprises (MSMEs). The normative juridical approach shows that the establishment of an Individual PT is feasible if it meets the requirements: it is declared a legal entity by law, has its own assets, and has government approval in accordance with Articles 153A and 153B of the Job Creation Law and Article 7 of Government Regulation Number 8 of 2021. The establishment process is carried out by filling out the establishment statement form in Indonesian and registering it with the Minister of Law and Human Rights to obtain a registration deed. However, supervision of Individual PT is still a challenge, because it does not have any other organs apart from the founder, so the potential for irregularities is greater. Therefore, new implementing regulations are needed to ensure legal certainty, guarantee supervision, and provide a clear responsibility mechanism for the actions of the founders and activities of PT Individuals. This is important so that PT Perorangan can function optimally as a legal entity that supports the development of MSMEs in Indonesia.